Societal Attitudes Towards Transgender Individuals: A Multicentric Survey Across Urban, Rural and Cosmopolitan Cities in India - Arokia Antonysamy; Amutha Govindaraju; Helena Selvakodi; Shanmugapriya Samiyappan (BJPsych Open)
Aims: The aim of this study is to investigate public attitudes towards transgender individuals, seeking to understand the relationship between socio-demographic factors, gender beliefs and approach towards this minority group. The research acknowledges the widespread stigma faced by transgender people due to the incongruence between their gender identity and sex assigned at birth, which negatively impacts their access to resources and overall well-being.